ANALISIS PENGUKURAN KUALITAS LAYANAN WEBSITE SIDEMANG PALEMBANG DENGAN METODE WEBQUAL 4.0 - Putri Sindi; Tri Oktarina (P3M Institut Teknologi Pagar Alam, 2023)
: In this era of globalization, the development of science and information technology has grown rapidly and continues to grow. Cominfo as government public relations, namely as a model of official program information or information that the government wants to convey to the public. SIDEMANG is an abbreviation of the Palembang Citizens Online Administration Information System. In measuring user satisfaction with a website, a method is needed to find out the final results which can later provide an overview to improve the quality of the website. The author uses the WebQual 4.0 method to conduct research. The Webqual 4.0 method is a continuation of the previous Webqual method which focuses on measuring website quality from the user's point of view. This study used a quantitative approach with data collection techniques through online questionnaires which were distributed to users of the Sidemang Palembang website. The research sample was taken from a total of 113 respondents through purposive random sampling. The data obtained were analyzed by factor analysis and multiple linear regression analysis. The results of the study show that the service quality of the Sidemang Palembang website is in a fairly good category. Based on factor analysis, user friendliness, information and interaction are the main factors that influence the service quality of the Sidemang Palembang website. Meanwhile, the results of hypothesis testing show that the usability factor and interaction quality factor have the greatest influence on the service quality of the Sidemang Palembang website. However, the data quality score does not affect service quality. This research can help to improve the service quality of the Sidemang Palembang website by knowing the factors that influence service quality. In addition, the results of this study can be used as a reference for the development of other similar online services.